2016 International Conference on Intelligent Systems Engineering (ICISE) 2016
DOI: 10.1109/intelse.2016.7475125
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of AAO membrane during the dialysis process

Abstract: In this paper we present structural simulation of 10×10 mm anodic aluminum oxide (AAO) membrane having thickness 0.5 mm by using ANSYS, that is finite element method based simulation software. AAO membranes have been used for various applications including hemodialysis, one of the most important applications in serving mankind. As the membrane is exposed to certain values of pressure during hemodialysis this may break or deform the membrane. Mechanical strength of AAO membrane was calculated by applying pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Theoretical studies have been done for testing the mechanical stability of AAO membranes for filtration application. The studies show that the membrane can bear pressure up to 0.79 MPa and is suitable for microdialysis [103]. An adaptive ultrafiltration layer has been designed using an AAO template in polyprotic to provide filtration properties and used for desoxyribonucleic acid analysis [104].…”
Section: Aao Membrane For Filtration 321 Applications Of Aao Membrane...mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies have been done for testing the mechanical stability of AAO membranes for filtration application. The studies show that the membrane can bear pressure up to 0.79 MPa and is suitable for microdialysis [103]. An adaptive ultrafiltration layer has been designed using an AAO template in polyprotic to provide filtration properties and used for desoxyribonucleic acid analysis [104].…”
Section: Aao Membrane For Filtration 321 Applications Of Aao Membrane...mentioning
confidence: 99%
“…The real-life conditions utilization during analysis helps estimate the results of pratical applications. These techniques may be efficient for more advanced applications with a reduction of cost of practical optimization of application [15,103,110].…”
Section: Applications Of Aao Membrane In Miscellaneous Fieldsmentioning
confidence: 99%
“…MW Ashraf et al [ 33 ] reported the controlled pore diameter fabrication of the AAO membrane using a two-step anodization process. MW Ashraf et al [ 34 ] investigated the suitability of the AAO membrane for dialysis by performing structural simulations. The results of this study suggest that the membrane can bear pressure up to 0.79 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, diabetes and ageing are the major cause of chronic renal failure, which gradually damages the kidney [3,4]. Nearly two million people globally receive renal failure treatment including renal transplant and dialysis [1,5]. Renal transplant is the best treatment for end stage renal failure, but due to lack of donor availability, tissue and blood group matching this treatment is considered to be a far approach for many patients.…”
Section: Introductionmentioning
confidence: 99%